MODEL PENGEMBANGAN KOMUNIKASI PEMASARAN DAN KUALITAS PRODUK DALAM RANGKA MERAIH KEPERCAYAAN DAN LOYALITAS KONSUMEN - Agus Budi Purwanto; Untung Widodo (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2016)
The background of this research is the lack of marketing communications and the quality of the products of UMKM in the city of Semarang. This indicates UMKM can not achieve the trust and loyalty of consumers. In general, this study aims to determine the effect of marketing communications and product quality on customer loyalty which the trust as an intervening variable. In particular, this study aims to improve the competitiveness of UMKM.The model used in this study is composed of four variables which at the first stage variable marketing communications and product quality into the independent variable, while the trust becomes the dependent variable. Then in the second stage of marketing communications and product quality as independent variables, the trust as intervening variables, while the variables of loyalty as the dependent variable data collection technique research by spreading questionnaires to consumers of SMEs in Semarang systematically arranged with multiple choice answers are easy to understand. Distribution of the questionnaire by means of a direct encounter conducted in the period April-July 2016 with a sample of 145 respondents. Then the data collected through questionnaires test data analyst; validity and reliability, continued with path analysis (Path Analysis), strength test model using SEM (Structural Equation Modelling).The research proves that there is a direct positive influence between marketing communications and quality produkk loyalty. The results also proved that trust is a positive intervening between marketing communications and product quality on customer loyalty